Comparison of three fresh cow feeding programs - W.F. Miller; Evan C. Titgemeyer; A.F. Park; M.V. Burgos (Kansas Agricultural Experiment Station Research Reports, 2003)
We evaluated the impact on performance of top dressing a based total mixed ration (TMR) with long-stem alfalfa hay with or without additional dry-rolled corn to the lactating cow diet during the first 5 days postpartum. The three dietary treatments and numbers of cows assigned to each diet were: 1) total mixed ration (TMR; n = 19); 2) TMR + long-stem alfalfa hay (TMR + A; n= 20); and 3) TMR + long-stemmed alfalfa hay + dry-rolled corn (TMR + A + C; n = 20). Top dressing the lactating TMR with long-stem alfalfa hay with or without dry-rolled corn did not reduce the incidence of metabolic disorders in early lactating cows. Six cows, two on each diet, were treated for displaced abomasums. Cows consuming only the TMR lost slightly more body weight during the first 30 days after calving compared to cows fed the other diets. Milk and energy corrected milk (ECM) yields were similar among diets. Fat, protein, and urea nitrogen content in milk were not different among dietary treatments. Lactose content in milk was greater for cows consuming TMR + A than those consuming TMR or TMR + A + C. Concentrations of glucose and urea nitrogen in plasma were not affected by treatment during the initial 5 days of lactation. Concentrations of glucose and urea nitrogen on days 2 and 3 were less for multiparous cows consuming TMR than for multiparous cows consuming TMR + A. Rumen contractions during the first 5 days of lactation were not different among diets. Top dressing the lactating TMR with long-stem alfalfa hay with or without dry-rolled corn was not beneficial in this study. On a dry matter basis, the lactating TMR contained 22% chopped alfalfa hay, 10% corn silage, 20% wet corn gluten feed, 9% whole fuzzy cottonseed, 7.1% expeller soybean meal, 27.4% ground shelled corn, 1.2% molasses, 1.3% Menhaden fishmeal, and 2.0% mineral-vitamin premix. Cows fed diets containing corn silage as the predominant fiber source may respond differently.; Dairy Day, 2003, Kansas State University, Manhattan, KS, 2003;
Keywords: Dairy Day; 2003; Kansas Agricultural Experiment Station contribution; no. 04-129-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 919; Dairy; Transition cows; Alfalfa; Dry-rolled corn